Investigating the Stirred Tank Bioreactor Co-Cultures of the Secondary Metabolite Producers Streptomyces noursei and Penicillium rubens - Tomasz Boruta; Anna Ścigaczewska; Marcin Bizukojć (Biomolecules, 2023)
The stirred tank bioreactor co-cultures of the filamentous fungus Penicillium rubens and actinomycete Streptomyces noursei were studied with regard to secondary metabolite (SM) production, sugar consumption, and dissolved oxygen levels. In addition to the quantitative analysis of penicillin G and nystatin A1, the broad repertoire of 22 putatively identified products was semi-quantitatively evaluated with the use of UPLC-MS. Three co-cultivation variants differing with respect to the co-culture initiation method (i.e., the simultaneous inoculation of P. rubens and S. noursei and the 24 or 48 h inoculation delay of S. noursei relative to P. rubens) were investigated. All the co-cultures were carried out in parallel with the corresponding monoculture controls. Even though S. noursei showed the tendency to outperform P. rubens and inhibit the production of fungal secondary metabolites, the approach of simultaneous inoculation was effective in terms of enhancing the production of some S. noursei SMs, namely desferrioxamine E, deshydroxynocardamine, and argvalin. S. noursei displayed the capability of adaptation and SM production even after being inoculated into the 24 or 48 h culture of P. rubens. Interestingly, S. noursei turned out to be more efficient in terms of secondary metabolite production when its inoculation time relative to P. rubens was delayed by 48 h rather than by 24 h. The study demonstrated that the prolongation of inoculation delays can be beneficial for production-related performance in some co-culture systems.